Kontibusi Kemandirian Siswa, Monitoring Orang Tua dan Fasilitas Kelas Terhadap Hasil Belajar Matematika - Ardiyanti, Siti Yuliana Nur; Novitasari, Meggy (Manajemen Pendidikan, 2018)
This study focuses on (1) examine the contribution of student independence, parentalmonitoring, and class facilities on mathematics learning outcomes (2) examinethe contribution of students’ independence on mathematics learning outcomes (3)examine the contribution of parental monitoring on mathematics learning outcomes(4) examine the contribution of class facilities on mathematics learning outcomes.This research belongs to quantitative research. The study population is 350students of class XI SMK Negeri 1 Miri Sragen. The study sample of 187 students isdetermined by the Slovin formula. The data are obtained using proportional randomsampling, questionnaire, and documentation. The data find in this research areanalyzed using multiple linier regression. The results of this study are (1) there is acontribution of student independence, parental monitoring and classroom facilitiestowards mathematics learning outcomes by 16.8% while the remaining 83.2% can be influenced by other factors outside this research (2) there is no contribution of students’ independence to mathematics learning outcomes with a relative contribution of 26% and an effective contribution of 4% (3) there is parental monitoring contribution to mathematics learning result with relative contribution of 18% and effective contribution 3% (4) there is a class facility contribution to mathematics learning outcomes with a relative contribution of 256% and an effective contribution of 9%.